PERKEMBANGAN BIOTEKNOLOGI MODERN KLONING (HASIL TEMUAN, RESIKO, DAN BIOETIKA DALAM PENELITIAN) - Nusantari, Elya (Sainstek, 2007)
Cloning is one of the Biotechnology branches advance that is developed by copying from male or female individual human being so it is got double identic genetic. The positive advantage from cloning that it is very good for cloning terapyutic, open new knowledge, save nutfah plasma, and avoid genetic disadvantage. In this category cloning can be developed so fort. Cloning risk in this case should be minimalized, cloning can be developed with a clear purposes, and cloning can be developed by research advance. In the case, Biotics in this research should be understood properly by experts so that it can be resulted research advantage that has good fuction for human and being prosperity